A new species of Lobocheilos (Teleostei: Cyprinidae) from East Kalimantan, Indonesian Borneo - Ciccotto, Patrick J.; Tan, Heok Hui (Zootaxa, 2018)
Lobocheilos aurolineatus, new species, is described from the Mahakam River basin in East Kalimantan, Indonesian Borneo. It is distinguished from all other species of Lobocheilos except for L. ixocheilos and L. tenura in having one pair of barbels (maxillary) and by the presence of a broad, black midlateral stripe, approximately ¾ scale height in thickness, extending from the operculum to the caudal-peduncle base. Lobocheilos aurolineatus differs from both species in possessing a thin cream to yellow stripe on the anterior ⅔ of the flank, separating the black midlateral stripe from the brown dorso-lateral scales, and by a smaller mouth width (23.5–29.9% head length in L. aurolineatus vs. 32.1–45.0% and 34.4–46.4% head length in L. ixocheilos and L. tenura, respectively).